Hubungan Kebiasaan Makan, Pengetahuan dan Pola Asuh Ibu dengan Kejadian Diare di Wilayah Kerja Puskesmas Liang Anggang Kota Banjarbaru - Hamdah, Isnaini Noor; magdalena, magdalena; Fathurrahman, Fathurrahman (Jurnal Skala Kesehatan, 2025)
Background Based on data from the Banjarbaru Health Service, the highest percentage of diarrhea in toddlers is at the Liang Anggang Health Center at 44.9% in 2022. The cause of diarrhea is multifactorial, mostly caused by infectious diseases. Objectives The aim of this research was to determine the relationship between eating habits, knowledge and parenting patterns of mothers with the incidence of diarrhea in toddlers in the work area of the Liang Anggang Community Health Center, Banjarbaru City. Methods This type of research is analytical observational, with a cross sectional design. The research was carried out in the work area of the Liang Anggang Community Health Center. The sample consisted of 41 toddlers taken by purposive sampling. Data collection uses questionnaires through interviews. Data analysis used the Spearman Rank Correlation test at α 0.05. Results The results of the research showed that toddlers' eating habits were good, namely 58.5%, mothers' knowledge was highest in the medium category, namely 46.3%, mothers' parenting patterns were still poor, namely 63.4%. There is a significant relationship between eating habits and the incidence of diarrhea (p=0.044). There is a significant relationship between maternal knowledge and the incidence of diarrhea (p=0.000). There is a significant relationship between maternal parenting patterns and the incidence of diarrhea (p=0.001). Conclusions It is recommended that mothers prioritize the cleanliness of water sources as well as storing water at home, maintaining food hygiene and knowing first aid for children with diarrhea.